Electron Distribution in AlGaN/GaN Modulation-doped Heterostructures - Thao, Dinh Nhu; Tien, Nguyen Thanh (Communications in Physics, 2013)
We present a calculation of the distribution of two-dimensional electron gas (2DEG)along the quantization direction in an AlGaN/GaN modulation-doped heterostructure (MDHS).The main conﬁnement sources from ionized donors, 2DEG and polarization charges are prop-erly taken into account. We show that the 2DEG distribution near the MDHS interface dependsstrongly on the model of potential barrier in use. Within the ideal model of inﬁnite potential bar-rier, the 2DEG distribution near the interface is increased with a rise of the sheet densities of2DEG and polarization charges. On the contrary, this distribution is decreased within the realisticmodel of ﬁnite potential barrier. Since the key mechanisms limiting the 2DEG mobility in MDHSare alloy disorder and surface roughness scatterings that are very sensitive to the near-interface2DEG distribution, with a rise of the sheet densities of 2DEG and polarization charges the 2DEGmobility is decreased within the inﬁnite-barrier model, while increased within the ﬁnite one.